Excavations in Area 2A at Sarūq al-Ḥadīd: Iron Age II evidence of copper production and ceremonial activities - Contreras Rodrigo, Fernando; Vila, Bernardo; Alabarracín, Pedro; Mohammed Bukhash, Rashad; Al Abbar, Sheikha Obaid; Radwan Karim, Mansour Boraik; Zein, Hassan Mohammed (Proceedings of the Seminar for Arabian Studies, 2017)
Sarūq al-Ḥadīd in al-Rubʿ al-Khālī in the Emirate of Dubai has been excavated since 2002 by several interdisciplinary teams. In this paper, we present the preliminary results of the work carried out in Area 2A by the Spanish team. This area, situated north-east of the site, provided a rich and varied set of archaeological materials that suggest the existence of metallurgical practices for copper smelting, as evidenced by a considerable amount of slag and some ore nodules. Finds of a few crucibles and some metallurgical tools, scattered through the area, suggest that smelting and possibly the manufacturing of artefacts were also carried out at the site. No metallurgical furnaces have been found so far. A very large number of copper-based objects, such as arrowheads, axes, and daggers, have been collected and it is tempting to propose that they were produced at Sarūq, although as yet no moulds have been identified. Both an apparent ritualized dispersion of these objects and the nature of some of the archaeological finds, including copper snakes, anthropomorphic figurines, soft-stone and alabaster vessels, point to the possible ceremonial and ritual nature of the site. The typology of these objects, complemented by pottery sherds and ¹⁴C analyses, provides an Iron Age II chronology for this site.